2021
DOI: 10.3390/foods10020344
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Properties of Cereal Vinegars

Abstract: Vinegar has been used for its health promoting properties since antiquity. Nowadays, these properties are investigated, scientifically documented, and highlighted. The health benefits of vinegar have been associated with the presence of a variety of bioactive components such as acetic acid and other organic acids, phenolic compounds, amino acids, carotenoids, phytosterols, vitamins, minerals, and alkaloids, etc. These components are known to induce responses in the human body, such as antioxidant, antidiabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 149 publications
(334 reference statements)
0
25
0
Order By: Relevance
“…The composition of vinegar is influenced by the raw material as well as the acetification process. Specifically, phenolic components affect both vinegar quality (colour, taste) and nutritional value; mainly its antioxidant capacity among other health benefits [ 22 , 23 ]. Table 2 presents the results of the analysis of TPC and AC of the vinegar made from the FSS sweet using the mixed A. aceti and K. europaeus culture, free and immobilized on DCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of vinegar is influenced by the raw material as well as the acetification process. Specifically, phenolic components affect both vinegar quality (colour, taste) and nutritional value; mainly its antioxidant capacity among other health benefits [ 22 , 23 ]. Table 2 presents the results of the analysis of TPC and AC of the vinegar made from the FSS sweet using the mixed A. aceti and K. europaeus culture, free and immobilized on DCM.…”
Section: Resultsmentioning
confidence: 99%
“…Benzothiazole has also been reported as a result of the thermal processing of Chinese vinegar [ 32 ]. Ligustrazine has been associated with the antioxidant, antimicrobial and other health benefits of vinegar [ 22 ]. Regarding L-menthol, 4-ketoisophorone, and p-cymen-8-ol, they have not been previously reported in vinegar.…”
Section: Resultsmentioning
confidence: 99%
“…Melanoidins have been extensively investigated for their health beneficial effects, and reports are signifying their other health beneficial properties. The beneficial health properties of food melanoidins are associated with various activities such as antioxidant, antimicrobial, anti-inflammatory, antihypertensive, and prebiotic activity ( 35 , 86 , 87 ). However, very few studies on the negative impacts of melanoidins on health are reported, an extensive review has been done on the impact of MRPs on nutrition and health by ALjahdali and Carbonero ( 61 ).…”
Section: Negative Health Impact Of Melanoidinsmentioning
confidence: 99%
“…Preventing hypertension requires a healthy diet, moderate exercise, no smoking, and reducing alcohol intake and stress [ 1 ]. A healthy diet consists of adequate energy intake to prevent obesity, salt reduction, increased fruit and vegetable intake, cholesterol/saturated fatty acid reduction, and increased polyunsaturated fatty acid and low-fat dairy product intake [ 2 ].…”
Section: Introductionmentioning
confidence: 99%